ChemInform Abstract: Phosphine‐Free Chiral Iridium Catalysts for Asymmetric Catalytic Hydrogenation of Simple Ketones. Issue 34 (4th August 2016) - Kumar, Prashant; Irrgang, Torsten; Kostakis, George E.; Kempe, Rhett
Abstract: Novel efficient and easily accessible pyridylalkylamine mononuclear iridium complexes are synthesized and utilized in the asymmetric hydrogenation of various ketones affording the corresponding alcohols.